Applied economic forecasting techniques - Hall, Stephen G. (New York : Harvester Wheatsheaf, 1994)
Surveys techniques in econometric time-series and macroeconomic modelling, illustrating the importance of forecasting to business and government. The book gives a detailed account of how a forecast is produced, the problems of data availability and the general influences which form a real forecast.
Includes bibliographical references (p. 191-206) and index.
nmn 11/7/17
Loans
Keywords: Economic forecasting; Forecasting techniques; Applied economic - forecasting